Provenance and paleoenvironmental significance of sediments in the Beipo seamount of the northern South China Sea during the last deglaciation - Tian, Xu; Zhang, Xilin; Wang, Jinli; Sun, Zhilei; Liu, Ming; Zhao, Jinhuan; Zhang, Lin; Fan, Dejiang; Xu, Fangjian (Frontiers in Marine Science, 2023)
The sedimentary process of seamount regions are closely related to climate change and ocean evolution. Clay minerals, grain size and AMS14C ages of core SCS18-1 collected from the Beipo seamount in the northern South China Sea (SCS) were analyzed to discuss the provenances and paleoenvironmental conditions during the last deglaciation. The sediments of core SCS18-1 are dominated by clayey silt, which is mainly composed of illite (55.2 62.1%) and chlorite (17.1 22.5%), with associated kaolinite (9.5 12.6%) and smectite (7.3 15.1%). The illite chemical index and illite crystallinity indicate strong physical weathering conditions. The results of the end-member modeling algorithm (EMMA) suggest that the sediments of core SCS18-1 consist of three end-members containing EM1 (0.98 μm), EM2 (9.29 μm) and EM3 (44.19 μm). The average contents of these three end-members are 3%, 66% and 31%, respectively. The finest endmember is interpreted as fluvial mud, and the middle and coarsest endmembers are interpreted as fluvial fine silt and eolian dust, respectively. The mean grain size is mainly controlled by the coarser fraction EM3. Since the last deglaciation period (16.1 ka BP), the sediments of core SCS18-1 mainly originate from fluvial input, and eolian input also contributes to the sediments. The content of clay minerals in core SCS18-1 is stable, mainly from Taiwan. Additionally, the Pearl River appears to be a secondary contributor of clay minerals. Further, the Luzon Islands only account for a small proportion. Major kaolinite and moderate illite and chlorite from the Pearl River, predominant illite and chlorite from Taiwan, and principal smectite from the Luzon Islands. The provenance and paleoenvironment in the seamount region are completely recorded by the sediments of core SCS18-1. Both the relative content of the EM1+ EM2 and the illite chemical index effectively represent the variation of East Asia summer monsoon (EASM) strength. Meanwhile, the relative content of EM3 effectively represents the East Asian winter monsoon (EAWM) change. The material supply of core SCS18-1 is mainly controlled by the solar radiation in the Northern Hemisphere.